2014
DOI: 10.1590/s0102-8650201400160004
|View full text |Cite
|
Sign up to set email alerts
|

MAPK immunoreactivity in streptozotocin-induced diabetic rat testis

Abstract: PURPOSE:To evaluate the alterations of two mitogen-activated protein kinases (MAPK)s, extracellular signal regulated kinase (ERK) and c-Jun NH2 terminal kinase (JNK), in the testes of male rats with experimental diabetes. METHODS:Twenty males Sprague-Dawley rats were randomly divided into a control group (n=8) and a diabetes group (administration of 40 mg/kg/day streptozotocin (STZ) for five sequential days, n=12). After six weeks, testicular biopsy samples were obtained for light microscopy and immunohistoche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
6
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 20 publications
11
6
0
2
Order By: Relevance
“…In T2DM mice, the prevalence was types h >g >d >f >b >c =e at 36 days, and it was types b >h >e >f >g >c >d at 72 days. The decreases in diameter and epithelial height of the seminiferous tubules of T1DM and T2DM mice in our study were similar to those found in previous reports [23,38,[42][43][44]. Our study also found a positive correlation between seminiferous tubule diameter and spermatogenesis along with decreased sperm concentration in the T1DM and T2DM mice.…”
Section: Discussionsupporting
confidence: 92%
“…In T2DM mice, the prevalence was types h >g >d >f >b >c =e at 36 days, and it was types b >h >e >f >g >c >d at 72 days. The decreases in diameter and epithelial height of the seminiferous tubules of T1DM and T2DM mice in our study were similar to those found in previous reports [23,38,[42][43][44]. Our study also found a positive correlation between seminiferous tubule diameter and spermatogenesis along with decreased sperm concentration in the T1DM and T2DM mice.…”
Section: Discussionsupporting
confidence: 92%
“…The observed tubular histopathology was classified into seven types ( Figure 6B-H ). The intraepithelial vacuolization found in this study is similar to that of previous studies in OHD-STZ rats ( 32 - 34 ). This type of histopathology is one of the most common injuries in Sertoli cells ( 35 ).…”
Section: Discussionsupporting
confidence: 91%
“…This type of histopathology is one of the most common injuries in Sertoli cells ( 35 ). Furthermore, the decreases in seminiferous tubule epithelium diameter found in this study were similar to those found in OHD-STZ rats ( 3 , 32 , 36 ).…”
Section: Discussionsupporting
confidence: 88%
“…Earlier studies showed that hyperglycaemia increases the expression of Bax protein as a pre-apoptotic gene and causes apoptosis in PC1 cells (Sharifi, Mousavi, Farhadi, & Larijani, 2007). In the testis of diabetic rats, apoptosis is accompanied with downregulation of Bcl-2 gene expression (Donmez, Kizilay, & Topcu-Tarladacalisir, 2014;Jafari Anarkooli, Sankian, Ahmadpour, Varasteh, & Haghir, 2008). This study revealed that treatment of diabetic rats with ADP extract prevented apoptosis through upregulating the expression of Bcl-2 protein.…”
Section: Discussionmentioning
confidence: 68%
“…The present results likewise showed lover testosterone level in diabetic rats. In the testis of diabetic rats, apoptosis is accompanied with downregulation of Bcl-2 gene expression (Donmez, Kizilay, & Topcu-Tarladacalisir, 2014;Jafari Anarkooli, Sankian, Ahmadpour, Varasteh, & Haghir, 2008). In this study, the Leydig cells of diabetic animals were assessed both quantitatively using physical discetor and qualitatively for Blc-2 expression.…”
Section: Discussionmentioning
confidence: 99%